Analysis of Formation of Sister Province International Cooperation - Ashar Prawitno; Achmad Rinaldy Jaharuddin; Rahmatullah Rahmatullah; Dian Ekawaty (Kemudi, 2022)
This research aims at how cooperation occurs in establishing international collaboration between the Provincial Government of South Sulawesi and Ehime Prefecture with areas of cooperation stated in the Memorandum of Understanding (MoU). This study used a qualitative descriptive approach with data obtained through library research, interviews, observations, and documentation, and eight informants were determined by purposive sampling. This study uses Dunn's (2004) theory; several things are needed, namely Problem Formulation, Forecasting, Recommendations, Observations, and Assessments, which are used to analyze the formation of Sister Province International Cooperation, South Sulawesi Provincial Government, and Ehime Prefecture, Japan. The results of this study indicate that so far, the coordination carried out with the Ministry of Home Affairs and Foreign Affairs is a flow that is by Government Regulation Number 28 of 2018. In establishing and implementing international cooperation with the South Sulawesi Provincial Government and Ehime Prefecture, there are several problems, including internal factors such as a change in the throne of leadership and miscommunication between the South Sulawesi Provincial Government and the agencies. Another problem is external factors, namely the Covid-19 pandemic and communication between the Provincial Government of South Sulawesi and Ehime Prefecture, which is not running smoothly, so this cooperation has not yet worked. In international cooperation, involving other parties who can make the collaboration successful is necessary.